2020
DOI: 10.3390/ijerph17072439
|View full text |Cite
|
Sign up to set email alerts
|

A Replication Study Identified Seven SNPs Associated with Quantitative Traits of Type 2 Diabetes among Chinese Population in A Cross-Sectional Study

Abstract: Genome-wide association studies (GWAS) have identified common variants for quantitative traits (insulin resistance and impaired insulin release) of type 2 diabetes (T2D) across different ethnics including China, but results were inconsistent. The study included 1654 subjects who were selected from the 2010–2012 China National Nutrition and Health Surveillance (CNNHS). Insulin resistance and impaired insulin release were assessed by homeostasis model assessment (HOMA). The study included 64 diabetes-related sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…RAS guanyl nucleotide-releasing protein (RASGRP) functions as a diacylglycerol DAG-regulated nucleotide exchange factor specifically activating Ras through the exchange of bound GDP for GTP. Although the genetic variants associated with RASGRP1 have been linked to both T1D and T2D 62 , 63 , the role of RASGRP1 in human β cells is largely unknown. Here, we found that loss of RASGRP1 , knockout of the regulatory region of RASGRP1, and risk allele of rs55728265 leads to increased β cell death.…”
Section: Discussionmentioning
confidence: 99%
“…RAS guanyl nucleotide-releasing protein (RASGRP) functions as a diacylglycerol DAG-regulated nucleotide exchange factor specifically activating Ras through the exchange of bound GDP for GTP. Although the genetic variants associated with RASGRP1 have been linked to both T1D and T2D 62 , 63 , the role of RASGRP1 in human β cells is largely unknown. Here, we found that loss of RASGRP1 , knockout of the regulatory region of RASGRP1, and risk allele of rs55728265 leads to increased β cell death.…”
Section: Discussionmentioning
confidence: 99%
“…MAEA is a membrane-associated E3 ubiquitin ligase subunit that is essential for the maintenance of hematopoietic stem cells and lymphatic potential; deletion of MAEA increases the expression of surface cytokine receptors in hematopoietic stem cells and impairs autophagy flux [ 100 ]. MAEA overexpression in primary mouse liver cells attenuates hepatic gluconeogenesis and reduces the risk of insulin resistance, which may improve type 2 diabetes mellitus [ 101 , 102 ]. MAEA is associated with low bone mineral density in postmenopausal women [ 103 ].…”
Section: Discussionmentioning
confidence: 99%